A sample assessment of records management practices in the University of the Philippines toward a development of a self-audit tool - Comia, Rechelle Olaguer; Olgado, Benedict Salazar (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2015)
For more than a hundred years as the leading university in the Philippines, the University of the Philippines (UP) has long struggled in managing its records. A number of studies on records management in the University confirm and illustrate this. The results of the assessment and self-audit conducted in this study, through the best practices of ISO 15489 and RA 9470, also suggest that same observation.
The self-audit tool measured that UP's compliance with ISO 15489 and RA 9470 is only at the low rate of 13%. Though the University achieved 24% for partial compliance on some of the provisions, the sum is still less than 50%. The very high rate of non-compliance (63%) should be a wakeup call to every stakeholder of the University that the conduct of a comprehensive study and formulation of immediate and long-term solutions about the current status of records management in the University are ardently needed. Moreover, the assessment highlights that UP: (1) has no official central records office; (2) has no established/in place records management program and common tools; (3) has no proper documentation of the established practices; (4) is unfamiliar with the provisions ISO 15489 and RA 9470; (5) has no systematic staffing pattern, with few qualified records officers who are not evenly distributed throughout its units, and constantly changing records personnel; (6) has no proper training program for its records personnel; (7) is struggling from a number of records issues, particularly the inadequate records storage; (8) failed to address the problems cited in earlier studies and neglected the recommendations stated therein; and, (9) has started to manage electronic records despite the current problematic management of paper records.
Given these, the University should then exert efforts on managing its records effectively as the problems associated with inefficient records handling deter smooth business transactions within the University and put the vital records of the University in peril.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines -- Records -- Evaluation; Records -- Management